Study Of Performance Appraisal Acceptane And Employees' Performance In Multinational Companies In Malaysia - Manshor, Amat Taap (2002)
The objectives of this study were to 1) develop valid measures of participation, goal setting, feedback, information quality, information validity, link performance with personnel decisions and fairness; 2) to develop valid and reliable measures of performance appraisal (PA) effectiveness scale, PA acceptance scale, and individual productivity scale; 3) to gauge the impact of participation , goal seeting, feedback, information quality , information validity, link performance with personnel decisions and fairness with performance appraisal acceptance and effectiveness, and employees' performance; 4) to identify the impact of demographic variables of respondents, performance appraisal characteristics and country of origin on performance appraisal acceptance and effectiveness and employees' performance.